2007
DOI: 10.1295/polymj.pj2006149
|View full text |Cite
|
Sign up to set email alerts
|

Unassociated Molecular Chains in Physically Crosslinked Gellan Gels

Abstract: ABSTRACT:It was demonstrated that gellan chains unassociated with the crosslinking domains in the gels are released from gellan gels into the external solution at 10 C. The concentration of released gellan chains in the external solution was estimated using a phenol-sulfuric acid method. The release of gellan chains was suppressed with increasing concentration of potassium chloride or calcium chloride in the external solution whilst it was enhanced with in-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 41 publications
2
13
0
Order By: Relevance
“…Therefore, the actual W d between the initial and final dehydrations could not be obtained ( W t / W d could not be determined). However, it is evident that the final W t / W d is larger than the initial one, which indicated that the swelling ratio increased by polymer elution during the repeated water exchanges 19. As shown in this figure, W t decreased and became constant after 20 days, which indicated that the elution almost stopped after 20 days.…”
Section: Resultsmentioning
confidence: 76%
“…Therefore, the actual W d between the initial and final dehydrations could not be obtained ( W t / W d could not be determined). However, it is evident that the final W t / W d is larger than the initial one, which indicated that the swelling ratio increased by polymer elution during the repeated water exchanges 19. As shown in this figure, W t decreased and became constant after 20 days, which indicated that the elution almost stopped after 20 days.…”
Section: Resultsmentioning
confidence: 76%
“…Although 0.15wt% kappa-carrageenan forms a gel in 0.2mol/dm 3 KCl, ten times more concentrated 1.5wt% kappa-carrageenan does not form a gel in 0.2mol/dm 3 NaI where kappa-carrageenan molecules form helices but these helices donot aggregate to form junction zones.…”
Section: Gelation Pointmentioning
confidence: 97%
“…This definition is limited to chemically crosslinked gels and excludes physical gels made by secondary molecular forces such as hydrogen bonds and hydrophobic interactions. It was found recently that some molecular chains in a gellan gel release out from the gel when it is immersed in a solvent such as water or salt solutions [3,4]. After a long time, the gel swells infinitely, and disperses completely in a great amount of water.…”
Section: Definition Of a Gelmentioning
confidence: 99%
“…[8][9][10][11] This elution phenomenon is characteristic of physically cross-linked gels. Recently, the elution from PVA cast gels has been measured quantitatively.…”
Section: Introductionmentioning
confidence: 99%